STRATEGI PENGELOLAAN SARANA DAN PRASARANA PENDIDIKAN DALAM MENDORONG MUTU SEKOLAH DI SMAN 1 WOJA KAB. DOMPU - Astarina Astarina; Sudirman Sudirman; Abdul Kadir Jaelani; Asrin Asrin; Mansur Hakim (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the strategies of planning, management, and supervision of educational facilities and infrastructure in improving the quality of education at SMAN 1 Woja, Dompu Regency. The research employed a qualitative approach with data collection techniques including in-depth interviews with the principal, vice principal of facilities and infrastructure, and teachers, supported by direct observation and documentation to strengthen the validity of the findings. The results indicate that the planning strategy has been carried out systematically based on the actual needs of the school, although it still faces limitations in facilities and funding; the management strategy has been implemented effectively through structured utilization, maintenance, and coordination; while the supervision strategy is conducted through administrative, structural, and participatory mechanisms that sustain the use of facilities, despite challenges in asset disposal processes. Overall, these three strategies contribute to creating a conducive learning environment and support the improvement of educational quality in the school.